TEAM GAMES TOURNAMENT LEARNING MODEL TO SOLVE THE MISSION IN SANDI HIZBUL WATHAN EXTRACURRUCULAR TO INCREASE LEARNING MOTIVATION - Fajriyatuz, Nurul; Setyosari, Punaji; Mashfufah, Aynin (Universitas Muhammadiyah Mataram, 2024)
Abstrak. Penelitian bertujuan untuk mengetahui efektifitas model team games tournament dalam pembelajaran Hizbul Wathan untuk meningkatkan motivasi belajar siswa. Jenis penelitian adalah kualitatif deskriptif, dengan metode pengumpulan data berupa observasi, wawancara, dan dokumentasi, menggunakan teknik purposive sampling dalam menentukan subjek penelitian serta teknik triangulasi sumber dalam menguji keabsahan data. Hasil penelitian ini adalah model pembelajaran TGT efektif dalam peningkatan motivasi belajar siswa SD Muhammadiyah 1 kota Malang. Siswa memiliki motivasi belajar yang tinggi, dibuktikan dengan antusiasme yang tinggi dan berpartisipasi aktif dalam proses pembelajaran serta pengembangan ketrampilan sosial pendapat forum, koordinadi kelompok, kerjasama mengatur kelompok.Abstract: The study aims to determine the effectiveness of the team games tournament model in Hizbul Wathan learning to increase student learning motivation. The type of research is qualitative descriptive, with data collection methods in the form of observation, interviews, and documentation, using purposive sampling techniques in determining research subjects and source triangulation techniques in testing the validity of data. The result of this study is that the TGT learning model is effective in increasing the learning motivation of students of SD Muhammadiyah 1 Malang. Students have high motivation to learn, as evidenced by high enthusiasm and active participation in the learning process as well as the development of social skills of forum opinions, group coordination, and cooperation in organizing groups.